Pre-discharge anemia as a predictor of adverse clinical outcomes in patients with acute decompensated heart failure - Kim, Min Chul (Korean J Intern Med, 2019)
BACKGROUND/AIMS: The impact of the timing of anemia during hospitalization on future clinical outcomes after surviving discharge from an index heart failure (HF) has been poorly studied in patients with acute decompensated heart failure (ADHF). METHODS: A total of 384 surviving patients with acute ADHF were divided into two groups: an anemia group (n = 270, 199 anemia at admission and 71 pre-discharge anemia) and a no anemia group (n = 114). All-cause mortality and HF re-hospitalization were compared between groups. RESULTS: During the follow-up period (median, 528 days), death occurred in 60 patients (15.6%) and HF re-hospitalization occurred in 131 patients (34.1%). Overall anemia was associated with increased mortality (hazard ratio [HR], 1.74; 95% confidence interval [CI], 1.03 to 3.01; p = 0.039), but not HF re-hospitalization (HR, 0.92; 95% CI, 0.59 to 1.42; p = 0.707). Pre-discharge anemia was significantly associated with increased mortality (HR, 1.68; 95% CI, 1.01 to 2.82; p = 0.048), but anemia at admission did not predict increased mortality or re-hospitalization. CONCLUSIONS: Pre-discharge anemia, rather than anemia at admission, was identified as an independent predictor of mortality in patients with ADHF after surviving discharge. The results of the present study suggest that the identification and optimal management of anemia during hospitalization are important in patients with ADHF.